2019
DOI: 10.12938/bmfh.18-015
|View full text |Cite
|
Sign up to set email alerts
|

IgA-enhancing effects of membrane vesicles derived from <i>Lactobacillus sakei</i> subsp. <i>sakei</i> NBRC15893

Abstract: Immunoglobulin (Ig) A in the mucus of the intestinal tract plays an important role in preventing the invasion of pathogenic microorganisms and regulating the composition of the gut microbiota. Several strains of probiotic lactic acid bacteria (LAB) are known to promote intestinal IgA production. Bacteria are also known to naturally release spherical membrane vesicles (MVs) that are involved in various biological functions such as quorum sensing, pathogenesis, and host immunomodulation. However, the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 31 publications
2
42
0
1
Order By: Relevance
“…[ 21–23 ] They possess various biological functions, including mediation of bacteria–bacteria communication and bacteria–host modulation. [ 24–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 21–23 ] They possess various biological functions, including mediation of bacteria–bacteria communication and bacteria–host modulation. [ 24–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Carasi et al [ 31 ] demonstrated an increase in IgA production along with inducing mucin, decreased expression of pro-inflammatory mediators and increased anti-inflammatory molecules following administration of L. kefiri CIDCA 8348 in healthy mice. Several authors observed that LAB significantly induces IgA secretion in the intestine [ 32 , 33 , 34 ] through an increase in the number of IgA + B cells in mice [ 35 ]. This is consistent with our current results, in which L. paracasei Ž2 alone significantly increased the level of IgA gene expression in all parts of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…MVs isolated from Bifidobacterium longum is internalized by mast cells in a phagocytosis-independent mechanism 64 , while MVs isolated from L. sakei subsp. sakei enhance IgA production by activation of Toll-like receptor 2 signalling 65 . Whether or not the MVs are taken up by the monocytes or interact solely with surface receptors, in our settings, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%